anonymous
  • anonymous
7x - 3y = 4 2x - 4y = 1 Which of the following systems is not the same as solving the system shown? 28x - 12y = 16 and -6x + 12y = -3 14x - 6y = 4 and -14x + 28y = 1 -28x + 12y = -16 and 28x - 56y = 14
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
7x−3y=4;2x−4y=1 Step: Solve 7x−3y=4 for x: 7x−3y+3y=4+3y(Add 3y to both sides) 7x=3y+4 7x7=3y+47(Divide both sides by 7) x=37y+47 Step: Substitute (37y+47) for x in 2x−4y=1: 2x−4y=1 2(37y+47)−4y=1 −227y+87=1(Simplify both sides of the equation) −227y+87+−87=1+−87(Add (-8)/7 to both sides) −227y=−17 −227y−227=−17−227(Divide both sides by (-22)/7) y=122 Step: Substitute (122) for y in x=37y+47: x=37y+47 x=37(122)+47 x=1322(Simplify both sides of the equation) Answer: x=1322 and y=122
welshfella
  • welshfella
you can do it this way look at each equation in one of the options if the equations are the result of multiplying each term by the same constant then the equations are the same do the above with each of the 3 sets
welshfella
  • welshfella
for example try option 1 28x - 12y = 16 is obtained by multiplying 7x -3y = 4 by 4

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

welshfella
  • welshfella
and -6x + 12y = -3 is obtained by multiplying 2x - 4y = 1 by -3 so the first option is the same as the original equations
welshfella
  • welshfella
so try options 2 and 3 the same way
welshfella
  • welshfella
to start you off the first equation in second set 7x - 3y = 4 is multiplied by 2 - did they do it correctly?
welshfella
  • welshfella
oh!! - talking to myself again!

Looking for something else?

Not the answer you are looking for? Search for more explanations.